Analysis of the efficiency level of the mozzarella cheese distribution channel (case study of CV Narendra Food Malang) - Miftakhurrizal Kurniawan; Tri Kurniawan Laksono; Mas'ud Effendi (AGROINTEK, 2025)
The distribution process has an essential role in the sustainability of an industry. The company's distribution process must be carried out effectively and efficiently, especially in terms of using human resources, capital, and others, to increase profits. Many companies need help with distribution efficiency, especially regarding CV Narendra Food. CV Narendra Food is a company that produces mozzarella cheese products with a short shelf life. The problem of short product shelf life requires companies to carry out effective and efficient distribution. The distribution process is currently experiencing issues related to efficiency. This study aims to measure the efficiency level of the distribution process carried out by CV Narendra Food and provide suggestions for improvement. This study uses the External Two-Stage Data Envelopment Analysis (DEA) model. The results showed that only two areas were efficient out of 8 distribution areas. Companies can make improvements by reducing distribution costs by using the services of delivery parties, increasing distribution in the regions that are considered inefficient, maximizing delivery to areas that are considered efficient, and setting a minimum number of orders so that deliveries can be made at optimal capacity.